Effects of Tapak Dara Leaves Extract on Kidney Histology of Aspartame-Induced Mice - Utami, Eva Tyas; Kurnia, Indah Salsabila; Mahriani, Mahriani (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2021)
This study aimed to determine the effect of Catharanthus roseus leaves extract on kidney histology of mice aspartame-induced. Mice were divided into 4 groups, namely the negative control group (K-) without treatment, the positive control (K+) given aspartame 0.02 mg/day, the dose group 1 (D1) was given aspartame 0.02 mg/day and continued with the C. roseus leaves extract at a dose of 0.42 mg/kg. Group 2 (D2) was given aspartame 0.02 mg/day followed by C. roseus leaf extract at a dose of 0.84 mg/kg BW. IP administered aspartame for 14 days, and C. roseus leaves extract was administered by gavage for 12 days. The data obtained were analyzed by One Way ANOVA and DMRT test with a significance level of 0.05. The results showed that the induction of aspartame at a dose of 0.02 mg/day in mice increased the average number of proximal tubular necrosis cells. Catharanthus roseus leaves extract administration at 0.42 mg/kg BW and 0.84 mg/kg BW for 12 days can reduce the number of proximal tubular necrosis cells in aspartame-induced mice. Thus it can be concluded that the administration of C. roseus leaves extract can reduce the proximal kidney tubules necrosis but has not been able to reach normal conditions yet.